Childhood Poverty Predicts Adult Amygdala and Frontal Activity and Connectivity in Response to Emotional Faces - Javanbakht, Arash; King, Anthony P.; Evans, Gary W.; Swain, James E.; Angstadt, Michael; Phan, K. Luan; Liberzon, Israel (Frontiers in Behavioral Neuroscience, 2015)
Childhood poverty negatively impacts physical and mental health in adulthood. Altered brain development in response to social and environmental factors associated with poverty likely contributes to this effect, engendering maladaptive patterns of social attribution and/or elevated physiological stress. In this fMRI study, we examined the association between childhood poverty and neural processing of social signals (i.e., emotional faces) in adulthood. 52 subjects from a longitudinal prospective study recruited as children, participated in a brain imaging study at 23-25 years of age using the Emotional Faces Assessment Task (EFAT). Childhood poverty, independent of concurrent adult income, was associated with higher amygdala and mPFC responses to threat vs. happy faces. Also, childhood poverty was associated with decreased functional connectivity between left amygdala and mPFC. This study is unique because it prospectively links childhood poverty to emotional processing during adulthood, suggesting a candidate neural mechanism for negative social-emotional bias. Adults who grew up poor appear to be more sensitive to social threat cues and less sensitive to positive social cues.